Structures and bonding of auropolyboroenes [Au2(B4)xB3]−, [Au2(B4)xB2]2− and [Au2(B4)xB]+ (x = 2, 3): comparison with dihydride polyboroenes. Issue 107 (15th October 2015) - Shao, Peng; Ding, Li-Ping; Lu, Cheng; Cai, Jiang-Tao; Liu, Bo; Sun, Chang-Bo
Abstract : Equilibrium structures of auropolyboroenes [Au2 (B4 ) x B3 ] −, [Au2 (B4 ) x B2 ] 2− and [Au2 (B4 ) x B] + ( x = 2, 3) are obtained from density functional theory-based calculations. Abstract : Equilibrium structures of auropolyboroenes [Au2 (B4 ) x B3 ] −, [Au2 (B4 ) x B2 ] 2− and [Au2 (B4 ) x B] + ( x = 2, 3) are obtained from density functional theory-based calculations. Results show that the ground states of Au2 B9 +, Au2 B13 + and Au2 B14 2− can be obtained by adding two Au atoms to the corresponding ground-state pure boron clusters. For Au2 B10 2−, Au2 B11 −, Au2 B14 2− and Au2 B15 −, the ladder structures are proven to be the ground states at TPSS, OVGF, and CCSD(T) levels, which is similar to that of dihydride polyboroenes. AdNDP analysis indicates that the two rows of boron atoms in these auropolyboroenes are bonded by delocalized three-, four-, or five-center σ and π bonds. Especially, the dominant bonding patterns in Au2 B11 − and Au2 B14 2− bear similarities to those of dihydride polyboroenes. The photoelectron spectroscopy (PES) spectra for anionic clusters were simulated to facilitate the experimental PES spectra. In addition, the fragmentation energies and products against different decay channels are estimated and discussed.